CHILDREN'S HEALTH PROTECTION IN INTERSECTORAL CONNECTION - Yu.E. Lapin (Вопросы современной педиатрии, 2008)
Recently discovered phenomenon of compensatory mechanism of absence of legislative durable national policy in health protection of children is described in this article. This mechanism was developed as a result of evolution of intersect oral connection for the sake of children's health protection. «National family policy», «national policy for the sake of children», «national policy in the field of circulation of narcotic, psychotropic substances and in the field of counteraction to its illegal use», «national policy of Russian federation in the field of education», «national policy in the field of labor relations» perform functions of such compensatory mechanism. Fact of regulation of social relations in the sphere of children's health protection with means of different active directions of national policy is evidence of legal assignment of a number of problems in children's health protection as real subject of policy. The negative feature of this problem is incomplete and fragmentary regulation of relationships in the field of children's health protection. This is the reason, which maintains a status of children's health protection service as passive dirigible object but not an active regulative factor.Key words: children, health, national policy.